Meta cognition – can we be aware of the process of our own learning – usage of neurofeedback - Grochowska, Irena (Studia Ecologiae et Bioethicae, 2014)
The human mind is the mediator of knowledge about the world because no human being has direct knowledge of their surrounding reality. All knowledge is „read and transported” by the brain and nervous system. Regardless of the progressive nature of the research into psychic phenomena, we are still faced with the mystery of what phenomena occur in the brain. The difficulties are mainly due to the interdisciplinary nature of cognitive science. Cognitive science as an interdisciplinary field, which attempts to explore the human mind and find a common area of research to unite all scientific research. Attempts to understand the mind constitute the most interdisciplinary task. Neuroscience is one of the disciplines that make up modern cognitive science. Neurobiology suggests the variety of processes that occur either in individual cells, the brain, and the nervous system, and the human body. Modern studies indicate the possibility of cognition of the brain in order to apply effective teaching and education. How does the brain learn? This question stimulates researchers to interdisciplinary cooperation in order to obtain a satisfactory answer. Recently there have been many new concepts related to research into the brain and methods that allow you to better utilize the potential of the brain in order to undertake a conscious process of self-discovery. The science of the brain is not only a part of medical science or biology but also disciplines such as pedagogy and didactics. The concepts neuroteaching, neurodidactics, and neurotechnologies are new, still relatively unknown, and unused. Reflecting on the conscious changes in the learning process, it is worth looking into the rules of biofeedback and neurofeedback and the possibilities of practically applying EEG biofeedback training, which is becoming a readily available method. Insightful observations of bioelectrical activity of the brain have led to naming multiple correlations between the mental state of individuals, their behavior, and EEG activity. Biofeedback, as a neurotechnological road to self-discovery, allows for the individual functions of the brain and body, previously considered involuntary, to become dependent on our will to a certain degree. Upon obtaining a higher degree of self-awareness, self-regulatory responses develop. Proponents of this method argue that self-regulation will become a major part of health care in the twenty-first century.